PENGARUH FAKTOR TERHADAP PERILAKU PENGELOLAAN KEUANGAN SYARIAH: PENDEKATAN SEM - Fifah, Nurul khafifah (Airlangga Journal of Innovation Management, 2024)
The high muslim population and the trend of halal living have resulted in increasing interest and growth in the islamic finance industry today. For every individual and company, financial management behavior is an important factor in making good financial decisions, especially in the context of Islamic finance. This research was conducted to find out whether factors such as sharia financial literacy, halal lifestyle, help seeking, locus of control, and sharia financial attitudes have an influence on sharia financial management behavior. This study involved 226 respondents from the JABODETABEK area who were at least 18 years old. The data were analyzed using SEM-PLS method. The results showed that all these factors have a positive correlation with sharia financial management behavior. However, when talking about a halal lifestyle, this research concludes that this halal lifestyle has a significant impact on sharia financial management behavior with sharia financial attitudes as moderation. The findings of this research provide important implications for the JABODETABEK region in developing strategies to increase sharia financial inclusion. Apart from that, this research can also be a reference for further research in the same field and contribute to a deeper understanding of related theories.